2020
DOI: 10.3389/fpsyt.2020.00132
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic Relationship Between Alexithymia and Interoceptive Accuracy, and Results From a Pilot Mindfulness Intervention

Abstract: Alexithymia, or a reduced ability to label and describe one's emotions, is a transdiagnostic construct associated with poor psychosocial outcomes. Currently, the mechanisms underlying affective deficits associated with alexithymia are unclear, hindering targeted treatment delivery. Recent research suggests deficient interoceptive awareness, or reduced awareness of one's internal bodily state, may be key in the etiology of alexithymia. It has long been demonstrated that mindfulness meditation can alter percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Mrs. A's alexithymia seems to have been relieved by the long-term MT as reported by Bornemann & Singer [24]. On the contrary, a brief MT had no signi cant effect on alexithymia [25]. In the present case, alexithymia was almost completely released by long-term MT.…”
Section: Experiential Avoidance (Ea) and Catharsissupporting
confidence: 75%
See 1 more Smart Citation
“…Mrs. A's alexithymia seems to have been relieved by the long-term MT as reported by Bornemann & Singer [24]. On the contrary, a brief MT had no signi cant effect on alexithymia [25]. In the present case, alexithymia was almost completely released by long-term MT.…”
Section: Experiential Avoidance (Ea) and Catharsissupporting
confidence: 75%
“…At the same time, she had a strange experience and a telepathic experience. The acquisition of interoceptive sense in MT is said to be closely related to the disappearance of alexithymia [25]. Her strange and telepathic experience could be a prelude to a mystical experience seen in meditation.…”
Section: Mindfulness-to-meaning Theory (Mtm Theory)mentioning
confidence: 98%
“…Other studies find no relationship between alexithymia and worse cardiac interoceptive accuracy [126] or better cardiac interoception in high alexithymia participants [127]. These inconsistent findings can be explained by a quadratic relationship between alexithymia and interoceptive accuracy; although many individuals with heightened alexithymia show low interoceptive accuracy, a subset of individuals with heightened alexithymia show abnormally high interoceptive accuracy in specific domains [128]. This may also speak to different subtypes of alexithymia, underscored by either attenuated or noisy augmented afferent signals.…”
Section: Measuring Dimensions Of Interoception In Mental Healthmentioning
confidence: 95%
“…Females also tend to have slower LHS characteristics than males (e.g., greater parental investment), similar to the pattern of sex differences seen in EA (Barrett et al, 2000; Ciarrochi et al, 2005; Wright et al, 2017). In addition, previous work has also linked LHS to both bodily/interoceptive awareness (Proffitt Leyva & Hill, 2018) and emotional intelligence (van der Linden et al, 2015), each of which have been linked to EA or the related construct of alexithymia (Aaron et al, 2020; Brewer et al, 2016; Herbert et al, 2011; Onur et al, 2013; Pollatos et al, 2005; Simmons et al, 2013; Smith, Lane, et al, 2018; Terasawa et al, 2014; Trevisan et al, 2019; Zaki et al, 2012). For example, Proffitt Leyva and Hill (2018) have suggested that individuals may develop low interoceptive awareness because they selectively allocate energy resources toward monitoring the conditions in the external environment, and therefore fail to monitor and learn from internal bodily and emotional states.…”
mentioning
confidence: 99%